Lactate Beyond a Waste Metabolite: Metabolic Affairs and Signaling in Malignancy - Baltazar, Fátima; Afonso, Julieta; Costa, Marta; Granja, Sara (Frontiers in Oncology, 2020)
To sustain their high proliferation rates, most cancer cells rely on glycolytic metabolism, with production of lactic acid. For many years, lactate was seen as a metabolic waste of glycolytic metabolism, however recent evidence revealed new roles of lactate in the tumour microenvironment, either as metabolic fuel or as signaling molecule. Lactate plays a key role in the different models of metabolic crosstalk proposed in malignant tumours: among cancer cells displaying complementary metabolic phenotypes, and between cancer cells and other tumour microenvironment associated cells, including endothelial cells, fibroblasts, and diverse immune cells. This cell metabolic symbiosis/slavery supports several cancer aggressiveness features, including increased angiogenesis, immunological escape, invasion, metastasis and resistance to therapy. Lactate transport is mediated by the monocarboxylate transporter (MCT) family, while another large family of G protein coupled receptors (GPCR), not yet fully characterized in the cancer context, is involved in lactate/acidosis signaling. In this mini-review, we will focus on the role of lactate in the tumour microenvironment, from metabolic affairs to signaling, including the function of lactate in the cancer-cancer and cancer-stromal shuttles, as well as a signalling oncometabolite. We will also review the prognostic value of lactate metabolism and therapeutic approaches designed to target lactate production and transport.